APPLICATION OF SAFETY-FIRST APPROACH TO MEASURE RISK BEHAVIOUR OF YAM FARMERS IN BENUE STATE, NIGERIA - I. P. Singh, N. K. Singh, Sanusi M. Sadiq; Lawal, M.; Ahmad, M. M.; Eije, O. C. (Journal of Scientific Agriculture, 2018)
The present research empirically measured the risk attitudes of yam farmers in Benue State of Nigeria. Multi-stage sampling design was used to draw a sample size of 120 respondents and ex-post 2016 production data were tacitly elicited from the respondents using structured questionnaire complemented with an interview schedule. The collected data were analyzed using both descriptive and inferential statistics. The yam sett was found to be the most important input in the production process, as such used to measure the farmers risk behavior. Evidence showed that all the respondents were risk aversive and the identified factor which propelled farmers’ risk apprehension was paucity of economic capital. Therefore, in order to shift the paradigm from risk aversion to risk preference, yam farmers in the studied area should be given access to formal credit facilities.